Settlement of Collective Labor Disputes: Conciliation and Arbitration - Pasco Cosmópolis, Mario (1983)
The legal mechanisms mainly used for the resolution of collective labor disputes are two: conciliation, where the parties attempt to reach an agreement voluntarily, and arbitration, which involves the intervention of an impartial third party to make a binding decision for both parties. Conciliation is also part and parcel of collective bargaining. To this extent, the existence of systems that stimulate direct negotiation should be encouraged, with the parties participating directly in the resolution of their issues. Accordingly, arbitration should only be supplementary, when conciliation fails. This leads us to a system of voluntary or conventional arbitration in disputes of a common or private nature, reserving forced or compulsory arbitration for those that affect essential public services, as well as those that are excessively prolonged in time or that compromise the economy or society of a country as a whole.